Planning prompts to promote uptake of HIV services among men: a randomised trial in rural Uganda. Issue 11 (30th November 2020) - Kavanagh, Nolan M; Schaffer, Elisabeth M; Ndyabakira, Alex; Marson, Kara; Havlir, Diane V; Kamya, Moses R; Kwarisiima, Dalsone; Chamie, Gabriel; Thirumurthy, Harsha
Abstract : Introduction: Interventions informed by behavioural economics, such as planning prompts, have the potential to increase HIV testing at minimal or no cost. Planning prompts have not been previously evaluated for HIV testing uptake. We conducted a randomised clinical trial to evaluate the effectiveness of low-cost planning prompts to promote HIV testing among men. Methods: We randomised adult men in rural Ugandan parishes to receive a calendar planning prompt that gave them the opportunity to make a plan to get tested for HIV at health campaigns held in their communities. Participants received either a calendar showing the dates when the community health campaign would be held (control group) or a calendar showing the dates and prompting them to select a date and time when they planned to attend (planning prompt group). Participants were not required to select a date and time or to share their selection with study staff. The primary outcome was HIV testing uptake at the community health campaign. Results: Among 2362 participants, 1796 (76%) participants tested for HIV. Men who received a planning prompt were 2.2 percentage points more likely to test than the control group, although the difference was not statistically significant (77.1% vs 74.9%; 95% CI –1.2 to 5.7 percentage points, p=0.20). The planning prompt was more effective among men enrolled ≤40 days before the campaigns (3.6 percentage-point increase in testing; 95% CI –2.9 to 10.1, p=0.27) than among men enrolled >40 days before the campaigns (1.8 percentage-point increase; 95% CI –2.3 to 5.8, p=0.39), although the effects within the subgroups were not significant. Conclusion: These findings suggest that planning prompts may be an effective behavioural intervention to promote HIV testing at minimal or no cost. Large-scale studies should further assess the impact and cost-effectiveness of such interventions.